2014
DOI: 10.1161/atvbaha.113.302832
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Arthritis in the Lewis Rat by Apolipoprotein A-I and Reconstituted High-Density Lipoproteins

Abstract: Objective— This study questions whether high-density lipoproteins (HDLs) and apolipoprotein A-I inhibit joint inflammation in streptococcal cell wall peptidoglycan-polysaccharide (PG-PS)–induced arthritis in female Lewis rats. Approach and Results— Administration of PG-PS to female Lewis rats caused acute joint inflammation after 4 days, followed by remission by day 8. The animals subsequently developed chronic joint inflammation that persisted until eu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 38 publications
0
34
1
Order By: Relevance
“…Our data demonstrate that rHDL's anti-inflammatory effects on LPS-stimulated BMDCs are mediated through interference with the MyD88/NF-κB pathway. Although the inhibitory actions of apoA-I and HDL on TLR signaling have been previously reported (19, 54), a mechanism by which HDL selectively impedes the MyD88-dependent signaling in DCs has not yet been established. Based on our findings we speculate that interaction of apoA-I on HDL with cell surface lipid transporters such as ABCA1 or SR-BI, leads to changes in downstream signaling events that in turn compromise NF-κB activation and transcriptional upregulation of Myd88 by LPS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data demonstrate that rHDL's anti-inflammatory effects on LPS-stimulated BMDCs are mediated through interference with the MyD88/NF-κB pathway. Although the inhibitory actions of apoA-I and HDL on TLR signaling have been previously reported (19, 54), a mechanism by which HDL selectively impedes the MyD88-dependent signaling in DCs has not yet been established. Based on our findings we speculate that interaction of apoA-I on HDL with cell surface lipid transporters such as ABCA1 or SR-BI, leads to changes in downstream signaling events that in turn compromise NF-κB activation and transcriptional upregulation of Myd88 by LPS.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, treatment of rats with an apoA-I mimetic peptide inhibited collagen-induced arthritis and reduced inflammatory cytokine levels (18). Moreover, administration of apoA-I or rHDL attenuated peptidoglycan-polysaccharide (PG-PS)-induced arthritis in Lewis female rats in an ABCA1-dependent manner (19). Although HDL modulates the activity of various immune cell subsets (12), the mechanism through which HDL regulates autoreactive T cell responses in vivo remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that PGPS can up-regulate TLR2 expression, which enhances inflammatory responses against infection (Komori et al, 2011; Wu et al, 2014). The enhanced inflammatory responses are involved in many factors, including inflammatory regulators and mucin during the development of OM (Han et al, 2009a; Han et al, 2009b; Roy et al, 2014; Trune and Zheng, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…This protocol causes most Tlr2 −/− mice death within three days (Han et al, 2009a), making it difficult to observe the long-term effect of OM. Peptidoglycan-polysaccharide (PGPS) of the bacterial cell wall can induce inflammation against bacterial infection by up-regulating TLR2 expression (Komori et al, 2011) and cause acute and chronic arthritis (Esser et al, 1985; Stimpson et al, 1987; Wu et al, 2014). Previous studies have shown that after clearance of Gram+ bacterial infection in the middle ears (MEs) by immune system, bacterial PGPS may be persistent in the MEs, causing COM (Fulghum and Brown, 1998; Komori et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…ApoA-I and reconstituted HDL have been shown to reduce inflammatory tissue injury by multiple mechanisms (128). As discussed in this review, HDL-associated proteins and lipids reduce I/R injury by preserving mitochondrial function.…”
Section: Discussionmentioning
confidence: 99%